Brass from the past : brass made, used and traded from prehistoric times to 1800 - Morton, Vanda, (Archaeopress Publishing Ltd., 2019)
Brass from the Past is a history of the use and production of brass, and more broadly an insight into the journey of this metal in the context of a changing and modernising world. The book follows the evolution of brass from its earliest forms around 2500 BC through to industrialised production in the eighteenth century. The story is told in the context of the people, economies, cultures, trade and technologies that have themselves defined the alloy and its spread around the world. It explores innovations, such as the distillation of zinc, that have improved the quality and ease of production. From national or religious priorities to exhaustion of raw material supplies, the themes from the past are echoed today. In the later centuries, the book shines a light on some of the more personal aspects of people,businesses and relationships that have influenced industry and its progress.